IMPLEMENTASI TEAM TEACHING TERHADAP PRESTASI BELAJAR SISWA SMA KELAS X SE-KOTA YOGYAKARTA PADA MATERI TRIGONOMETRI - Sri Adi Widodo (Universitas Sarjanawiyata Tamansiswa, 2013)
This research was formed the background by the low level of the studying achievement of the student's mathematics was caused by the negative perception of the student towards mathematics, the object studying in mathematics abstract was not yet realistic and studying that was used did not yet use the teacher and the capacity of the study field to understand the concept of mathematics in the level was beforehand very weak. The aim of this Research was to know that was effective used in studying, with team teaching or individual teaching . This research used the method of the quasi experiment. The research population was all the student class X the Senior High School inYogyakarta in the year 2010-2011. The sample that was used in this research 2 schools. The taking of the Sample was carried out technically cluster random sampling. The instrument test was carried out used the validity test, the level of the difficulty of the difference power and reliabilitas. Technically the analysis that was used t-test. As the condition for the analysis that is the population normal distribution, and the population had the same variance (homogeneous). In this research could be concluded that studying the team to the study field of mathematics not yet effective was applied to the student class X the senior high school in Yogyakarta with the subject of discussion Trigonometry. This could be seen from results of the t-test that was received (tobs) of 1,145 where the area of criticism in u = 236 in the level siginificans 5% (two sides) is .